Engineering RENTA, a DNA prime-MVA boost HIV vaccine tailored for Eastern and Central Africa. - Nkolola, J; Wee, E; Im, E; Jewell, C; Chen, N; Xu, X; Mcmichael, A; Hanke, T (2004)
For the development of human immunodeficiency virus type 1 (HIV-1) vaccines, traditional approaches inducing virus-neutralizing antibodies have so far failed. Thus the effort is now focused on elicitation of cellular immunity. We are currently testing in clinical trials in the United Kingdom and East Africa a T-cell vaccine consisting of HIV-1 clade A Gag-derived immunogen HIVA delivered in a prime-boost regimen by a DNA plasmid and modified vaccinia virus Ankara (MVA). Here, we describe engineering and preclinical development of a second immunogen RENTA, which will be used in combination with the present vaccine in a four-component DNA/HIVA-RENTA prime-MVA/HIVA-RENTA boost formulation. RENTA is a fusion protein derived from consensus HIV clade A sequences of Tat, reverse transcriptase, Nef and gp41. We inactivated the natural biological activities of the HIV components and confirmed immunogenicities of the pTHr.RENTA and MVA.RENTA vaccines in mice. Furthermore, we demonstrated in mice and rhesus monkeys broadening of HIVA-elicited T-cell responses by a parallel induction of HIVA- and RENTA-specific responses recognizing multiple HIV epitopes.